Analysis of Community-Based Awareness Regarding Schizophrenia: A Cross-Sectional Study from Pakistan: Community-Based Awareness Regarding Schizophrenia - Mohsin, Hareem; Aslam, Muhammad Kamran; Fatima, Kaneez; Asif, Azka; Fiaz, Amal; Ahmad, Bushra; Khalid, Afeefa; Fatima, Warda (Pakistan Journal of Health Sciences, 2022)
Schizophrenia is a serious mental disorder and general public usually show unfavorable attitudes towards the patients. Objective: The study assesses the extent of public knowledge about Schizophrenia, a mental illness, among Pakistan's educated population and to recommend ways to create a better society for the patients and caretakers. Methods: 500 participants voluntarily took part in the study. A questionnaire was developed and a cross-sectional survey was conducted among the respondents. Participants were asked questions related to general, medical, socioeconomic, and treatment information of schizophrenia. Data analysis was done using SPSS software via T/F tests and Chi-square analysis. Results: It was revealed that overall females were more aware of mental illness as compared to males. The age groups of 18-22, 23-27 and 33-37 and participants with graduate and post-graduate degrees were having more knowledge regarding general, medical, socioeconomic, and treatment categories. Upon analysis via chi-square using SPSS, null hypotheses were accepted. Conclusions: Despite of the people having knowledge regarding schizophrenia, there is a significant percentage of populace which is not aware. Seminars, workshops, and campaigns must be conducted to enhance the knowledge of the general public to put an end to this stigma from society which will help in giving better care to the patients.